Justice Derailed: Navigating the Turbulent Waters of Pakistan’s Judiciary through the Ages - Abdul Qayyum Gondal,; Prof. Dr. Matloob Ahmad (Corresponding Author),; Zulkarnain Hatta,; Dr. Muhammad Imtiaz,; Mubashar Hasnain, (Al-Qanṭara, 2023)
The judicial system in Pakistan has a rich historical evolution spanning over a millennium, including significant epochs like the Hindu era, Muslim period, British colonial rule, and post-independence developments. The objective of this paper is to understand the complexity and shortcomings that have defined Pakistan's legal system through a comprehensive and critical analysis of the country's judicial history. With a focus on Pakistan's early years of independence, it sheds light on the difficulties of building judicial independence and a strong legal framework by delving into the historical growth of the judiciary and drawing inspiration from influential publications. The research methodology is multifaceted and combines legal analysis, historical research, and critical assessment to identify the underlying causes of the perceived shortcomings in Pakistan's judicial history. Using this historical basis, the study has critically examined the situation of the judiciary today, placing a strong emphasis on constitutional analysis to highlight the discrepancy between the goals of the Constitution and their actual application. The research contributes to a more nuanced understanding of the difficulties facing the judiciary by identifying anomalies and flaws in the decision-making process through the examination of major cases. It calls for a thorough examination of sociological viewpoints, practical difficulties, judicial corruption, public opinion, and the function of technology. As a result, this paper offers a forward-looking viewpoint and lays the groundwork for upcoming conversations and initiatives targeted at changing Pakistan's legal system.